West Nile Fever in the central part of Ukraine - Kotelevska, T. M.; Pryimenko, N. O.; Dubynska, H. M.; Koval, T. I.; Iziumska, O. M.; Zviagolska, I. M. (Medicni Perspektivi, 2020)
WestNileFever (WNF) is the most common arbovirus infection with a transmission mechanism caused by West Nile Virus (WNV), present on all continents, except for Antarctica. WNVhas a high epidemic potential and is dangerous for health of the population all over the world, due to rapid global spread, the formation of new natural foci and the ability to cause epidemics in endemic areas. Over the past 20 years, there have been numerous epidemic outbreaks of the disease among people, birds and horses, associated with WNV.On the territory of Ukraine WNV was first detected in the 70s of the XX century, but at present clinical and epidemiological aspects have been understudied.This study analyzed the epidemic situation regarding WNF in Poltava Region in 2011-2018, and clarified the epidemiological and clinical manifestations of serologically confirmed cases of acute WNF. This is the first actual survey of WNF cases in Poltava Region, its results indicate the prevalence of WNV in the central part of Ukraine. The aim of the study was to study the epidemiological and clinical characteristics of West Nile Fever in Poltava Region.The cases of WNF in Poltava Region in 2011-2018 have been analyzed, according to the annual reporting forms of the Ministry of Health of Ukraine. A serological study of pair blood sera for specific IgG-class antibodies to WNV of 232 patients with febrile conditions, requiring screening for WNF,was conducted. The clinical course was studied in a retrospective analysis of 14 case histories of patients with WNF under treatment in the Poltava Regional Clinical Infectious Diseases Hospital.The analysis demonstrated that in Poltava Region in 2011-2018 35 serologically confirmed cases of acute WNF were registered, with the largest number (14) in 2012.Serologic examination of the specific markers of WNV in 232 patients with febrile conditions allowed to detect 57 (24.6%) seropositive patients.Acute WNF was diagnosed in 35 (15,1%) patients, past WNF – in 22 (9,5%) persons.Analysis of case histories of patients with acute WNF showed that the most susceptible ones were females (64.1%), and the average age of the persons was 46.28±0.30 years old.According to the epidemiological history, the city residents dominated among the patients (71.4%), all of them (100%) marked mosquito bites, and the disease was of a seasonal nature, with the largest (78.6%) number of cases in July-August. The clinical course of WNF in all (100%) patients was moderate-severe and characterized by polymorphism of clinical manifestations.The leading clinical syndromes were: intoxication (100.0%), fever (100.0%), catarrhal (50.0%), allergic (42.8%), dyspeptic (35.7%) syndromes and lymphadenopathy (28.5 %). Thus, the conducted researches have shown that there are all conditions for formation of a natural center of WNF on the territory of Poltava Region. WNF was characterized by a typical course of the disease.